Penerapan Artificial Intelligence dalam Menunjang Pemahaman Matematika Siswa SD - Naji Maulana; Rangga Raihan Saputra; Ilham Zaenal Misbah; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article discusses the role of Artificial Intelligence (AI) in supporting elementary school (SD) students' understanding of Mathematics subjects. Using the Systematic Literature Review (SLR) method, this research analyzes various literature to describe the potential of AI technology in adaptive, interactive and personalized learning. The results show that AI makes a significant contribution to improving understanding of mathematical concepts, but also faces challenges in its implementation. Therefore, this research recommends a strategic approach to integrating AI into the basic education system.